Comprehensive analysis of stroke epidemiology in Vietnam: Insights from GBD 1990–2019 and RES-Q 2017–2023 - Minh Cong Tran; Lara Prisco; Phuong Minh Pham; Huy Quoc Phan; Mario Ganau; Nhat Pham; Linh Huyen Truong; Proochista Ariana; Phuong Viet Dao; Dung Tien Nguyen; Chi Van Nguyen; Hoa Thi Truong; et al. (Global Epidemiology)
Background: Stroke is a significant health burden in Vietnam, with substantial impacts on mortality, morbidity, and healthcare resources. An up-to-date report on stroke epidemiology and associated risk factors in Vietnam was missing. Method: We analyzed the data published in the Global Burden of Disease (GBD) 2019, in combination with the first-time analysis of the Registry of Stroke Care Quality Improvement (RES-Q) initiative in Vietnam from 2017 to 2023. Findings: Comparative analysis globally revealed that Vietnam had one of the highest stroke incidence and prevalence rates in Southeast Asia and ranked 4th in stroke mortality among 11 neighbouring countries. In the RES-Q dataset, 95,696 patients (77 %) were ischemic stroke, 23,203 (18 %) were intracerebral haemorrhage, and 2816 (2 %) were subarachnoid haemorrhage. In GBD 2019, stroke was the leading cause of death among cardiovascular diseases in Vietnam, accounting for 135,999 fatalities. The incidence of stroke was 222 (95 % UIs 206–242) per 100,000 population, with a prevalence of 1541 (1430-1679) per 100,000. Results align with the report from the RES-Q dataset in two megacities of Vietnam: Hanoi (incidence rate of 168.9, prevalence rate of 1182.2) and Ho Chi Minh City (incidence rate of 207.1, prevalence rate of 1221.8). Key risk factors for stroke mortality are high systolic blood pressure (79,000 deaths), unhealthy dietary (43,000 deaths), high fasting plasma glucose (35,000 deaths), and air pollution (33,000 deaths). Incidence is lower in rural Vietnam, but availability and quality of care are higher in megacities. Interpretation: The results promote a further understanding of stroke and risk factors for the Vietnamese population and suggest prevention and treatment strategies for the Vietnamese government, including facility and capacity improvement and applications of advanced technologies.